Analisis Efisiensi Saluran Pemasaran Ikan Nila di Desa Kupang Kecamatan Lampihong Kabupaten Balangan (Studi Kasus Pada Kelompok Perikanan Kupang Maju) - Meldasari Meldasari; Ahmad Suhaimi; Rachman Fitrianoor (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
This study aims to determine the marketing channels and institutions involved in the marketing of tilapia in Kupang Village, Lampihong Subdistrict, Balangan Regency, to know the structure of the tilapia market, analyze costs, profits, marketing margins and the price portion received by producers. This research was done intentionally by the census method and case study research design and data collection by interview. The results showed four marketing channels for tilapia, namely I: cultivators and collectors, II: cultivators, collectors, and retailers, III: cultivators, collectors and wholesalers and IV: farmers, traders, wholesalers and retailers. Market structure is monolithic competition. The total marketing channel I channel is IDR 11,000 per kg, the portion of the price received by farmers is 67.64%, the marketing cost is IDR 1,335 per kg and the profit gained is IDR 9,665 per kg; channel II's total marketing margin is Rp. 17,000 per kg, the portion of the price received by farmers is 57.5%, the marketing cost is Rp. 3,785 per kg, and the profit received is 13,215 per kg; total channel III marketing margin is Rp. 17,500 per kg, part of the price received by farmers is 56.79%, marketing costs Rp. 3,192.5 per kg and profits received Rp. 14.307.5 per kg; total channel IV marketing margin is Rp. 15,000 per kg, part of the price received by farmers is 60.52%, marketing costs Rp. 6,385 per kg and profits received 9,855 per kg. Channel I efficiency value: 3.92%, II; 9.46%, III: 7.88%, and channel IV, which is 16.80%. Channel I is the most efficient because the marketing institution is smaller, namely 3.92%.